2020
DOI: 10.1039/c9cp06995j
|View full text |Cite
|
Sign up to set email alerts
|

Transient IR spectroscopy identifies key interactions and unravels new intermediates in the photocycle of a bacterial phytochrome

Abstract: Infra-red spectroscopy advances our understanding of how photosensory proteins carry their function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 53 publications
8
33
0
Order By: Relevance
“…Such a CI is reached through a counterclockwise rotation of the D-ring with a hula-twist mechanism, resulting in a structure that is here interpreted as the early Lumi-R intermediate. Notably, this intermediate is characterized by the interaction of the chromophore D-ring with a tyrosine residue (Tyr263) in line with mutational studies 38,46 that demonstrated the tight connection between Tyr263 and the chromophore state. The IR spectrum calculated on the proposed structure shows a good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Such a CI is reached through a counterclockwise rotation of the D-ring with a hula-twist mechanism, resulting in a structure that is here interpreted as the early Lumi-R intermediate. Notably, this intermediate is characterized by the interaction of the chromophore D-ring with a tyrosine residue (Tyr263) in line with mutational studies 38,46 that demonstrated the tight connection between Tyr263 and the chromophore state. The IR spectrum calculated on the proposed structure shows a good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 53%
“…We assign this conformation to the early Lumi-R state. Mutagenesis studies 38,46 have suggested that the Y263F mutation hinders the formation of Lumi-R, thereby reducing the photoconversion (Pr→Pfr) yield: our simulations show that Tyr263 is indeed fundamental for stabilizing the Lumi-R state through a hydrogen bond with the N D atom of BV.…”
Section: 71mentioning
confidence: 63%
“…Mutational studies have identified highly conserved key amino acids (e.g., Y133, Y47, D79 and H160 in Syn Cph2 or Y263, Y176, D207 and H290 in Syn Cph1 and DrBphP) in the immediate vicinity of the D-ring that directly affect the excited state lifetime and the isomerization quantum yield [ 10 , 13 , 36 , 42 , 60 , 61 , 62 , 63 ]. In case of the Tyr residues both their steric interactions with the chromophore as well as their participation in the hydrogen bonding network have been proposed as essential for efficient photochemistry [ 60 , 62 , 63 , 64 , 65 ]. Additionally, solvent exposure, the overall hydrogen bonding network and the protonation state of several residues inside the pocket also appear to be important for its properties [ 34 , 36 , 42 , 43 , 60 , 61 , 66 ] and the ensuing kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…The understanding of the phytochrome family has been largely driven by experimental studies employing IR, 20 resonance Raman, 21 24 NMR, 25 and X-ray crystallography. 17 , 26 29 In contrast to other photoactive systems such as rhodopsin and photoactive yellow protein, there are few recent computational studies attempting to determine how the signal is relayed from the chromophore to the protein matrix.…”
Section: Introductionmentioning
confidence: 99%
“…However, this goal poses a major difficulty due to the so-called the Boltzmann sampling problem 39 caused mainly due to the existence of long time scales involved in the dynamics of photoproducts. 20 To achieve such a challenging goal, we employ enhanced sampling MD simulations to overcome the FE barrier of the primary photoisomerization event and to efficiently sample nonequilibrium configurations visited by the BphP-BV complex in the Pr and Pfr conformers. By performing simulations with an aggregate time of ∼2 μs, we study the Pr and Pfr conformers starting from their equilibrium configurations, i.e., before the photoisomerization takes place (Pr) and after the primary photochemical event is concluded (Pfr).…”
Section: Introductionmentioning
confidence: 99%